2020
DOI: 10.22438/jeb/41/5/mrn-1246
|View full text |Cite
|
Sign up to set email alerts
|

Ionizing radiation mediated effect on morphological, biochemical and microsporogenesis behavior of Artemisia annua L.

Abstract: To evaluate the effect of gamma rays on the cytological, morphological and biochemical aspects of Artemisia annua L. 60 Fresh seeds of Artemisia annua L. were treated with gamma rays (100 Gy, 200 Gy, 300 Gy& 400 Gy) through a Co source. Along with one set of control, the seeds were sown in triplicates to raise population for meiotic study. Mature capitula were collected for pollen study. Mutagen sensitivity was also studied using morphological (germination percentage, survival percentage, plant height and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…The trend observed in plant height indicated that lower doses of irradiation were beneficial and resulted in more favorable responses. Similar findings have been reported by Kumar and Mishra (2020) in Bhringraj and Kumar & Singh (2020) in Artemisia annua. Ali et al (2016) have proposed that lower doses of gamma rays can stimulate plant growth by enhancing the antioxidative capacity of cells or by modulating hormonal signalling.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The trend observed in plant height indicated that lower doses of irradiation were beneficial and resulted in more favorable responses. Similar findings have been reported by Kumar and Mishra (2020) in Bhringraj and Kumar & Singh (2020) in Artemisia annua. Ali et al (2016) have proposed that lower doses of gamma rays can stimulate plant growth by enhancing the antioxidative capacity of cells or by modulating hormonal signalling.…”
Section: Discussionsupporting
confidence: 91%
“…They reported that the rate was directly proportional to the irradiation dose. Kumar and Singh (2020) also reported the same pattern in Artemisia annua. Jagtap & More (2014) have analyzed the same output on Lablab purpureus and concluded that sterility in the plants enhances vigorously as the dose of physical or chemical mutagen increases.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Therefore, this study explores the differences in the NO 3 − -N and NH 4 + -N contents of tillage soil and in the growth status and yield of cotton plants under different N conservation measures in the extremely arid Tarim Basin in Xinjiang, China. Reducing the N dosage in fertilizers without reducing the cotton yield and the N utilization efficiency has important implications for the management of cotton fields and for decreasing non-point source N pollution in arid areas [24][25][26].…”
Section: Introductionmentioning
confidence: 99%